Ethnopedagogic Based Teaching Materials Analysis For Senior High School Students: A Literature Riview - Tugiyati, Tugiyati; Wiyanto, Wiyanto; Lisdiana, Lisdiana (Journal of Innovative Science Education, 2021)
Learning process at senior high school still based on textbook oriented. It makes students less concerned with the environment especially the school environment where they study. Such condition requires a real action to solve so that the level of environmental awareness of the students is increased. This research aims to determine the relevance of research on teaching materials, ethnopedagogics, and environmental awareness character as well as the effectiveness of ethno pedagogic-based-teaching materials on environmental awareness character for senior high school students based on literature review. This research uses the literature review method to obtain the data. Teaching materials provide added value when sourced from the environment around the school (ethnopedagogic). Ethnopedagogy–based-teaching materials will increase character cares for the environment of high school students.